Nucleomorph Small RNAs in Cryptophyte and Chlorarachniophyte Algae. (5th April 2019) - Åsman, Anna K M; Curtis, Bruce A; Archibald, John M
Abstract: The regulation of gene expression and RNA maturation underlies fundamental processes such as cell homeostasis, development, and stress acclimation. The biogenesis and modification of RNA is tightly controlled by an array of regulatory RNAs and nucleic acid-binding proteins. While the role of small RNAs (sRNAs) in gene expression has been studied in-depth in select model organisms, little is known about sRNA biology across the eukaryotic tree of life. We used deep sequencing to explore the repertoires of sRNAs encoded by the miniaturized, endosymbiotically derived "nucleomorph" genomes of two single-celled algae, the cryptophyte Guillardia theta and the chlorarachniophyte Bigelowiella natans . A total of 32.3 and 35.3 million reads were generated from G . theta and B . natans, respectively. In G. theta, we identified nucleomorph U1, U2, and U4 spliceosomal small nuclear RNAs (snRNAs) as well as 11 C/D box small nucleolar RNAs (snoRNAs), five of which have potential plant and animal homologs. The snoRNAs are predicted to perform 2′- O methylation of rRNA (but not snRNA). In B . natans, we found the previously undetected 5S rRNA as well as six orphan sRNAs. Analysis of chlorarachniophyte snRNAs shed light on the removal of the miniature 18–21 nt introns found in B . natans nucleomorph genes. Neither of the nucleomorph genomes appears to encode RNA pseudouridylation machinery, and U5 snRNA cannot be found in the cryptophyte G. theta . Considering the central roles of U5 snRNA and RNA modifications in other organisms, cytoplasm-to-nucleomorph RNA shuttling in cryptophyte algae is a distinct possibility.